20.4: Distinguished Paper: Quantum‐dot Light Emitting Diodes with Charge Generation Layers. Issue 1 (June 2015) - Kim, Hyo-Min; Kim, Jeong-Gi; Lee, Ji-Eun; Jang, Jin
Abstract : We report the solution processed charge generation layers (CGLs) used for inverted quantum‐dot light emitting diodes (QLEDs). The inverted green, yellow and red QLEDs with solution processed CGLs exhibit the maximum current efficiency (CEmax ) of 19.2, 13.6 and 6.1 cd/A, respectively. Therefore, solution processed CGL can be used for low cost QLEDs with high efficiency.